Perbandingan Hukum Tentang Pelecehan Seksual Terhadap Hewan Dengan Kuhp Indonesia Dan Kuhp Laos Criminal Code - Pamungkas, Sekar Langit Jatu; Kuswardani, Kuswardani (Prosiding University Research Colloquium, 2021)
The Criminal Code (KUHP), which is a legacy of the Dutch colonial government, is no longer relevant to changes and developments in society, especially if it is related to the diversity of types of sexual harassment as deviant sexual behavior which no longer makes fellow humans victims but has extended to a number of animal species. A special comparison is needed to find out the legal arrangements regarding sexual harassment of animals in order to find out whether Indonesia’s legal system is better or worse. Laos is one of Indonesia’s neighboring countries which is within the scope of the Southeast Asia region where the legal system used is also different and can be used as an appropriate comparison to know in this study. So that it can be compared with each other which criminal law system is better in achieving justice as one of the goals of implementing a law. The research method used in this research is the normative juridical law research method. The results of the research show that the provisions of the criminal law rules in each KUHP which are enforced as a source of criminal law for the Indonesian state and criminal regulations in Laos as a comparison, it is known that in their application, both The applicable criminal law system does not clearly and specifically regulate sexual harassment behavior against animals.